The (Ir)Relevance of Audience Studies in Journalism Education. (June 2022) - Nelson, Jacob L.; Edgerly, Stephanie
Journalism stakeholders increasingly believe that they need to better understand the news audience to accomplish their goals. Our study explores the extent to which this "audience turn" has unfolded in the education of future journalists. Drawing on data collected from course syllabi from leading journalism schools throughout the United States, we find that few journalism courses include aspects focused on news audiences. Those that include readings and/or assignments relating to news audiences maintain a narrow focus on audience metrics. We conclude by discussing what these trends mean for the future of journalism and the audience gap in journalism education.